Tipu Sultan in History: Revisionism Revised - Narasingha Sil (SAGE Open, 2013)
This historiographical essay seeks to chart a middle course between what may be called Tipu bashing and, to borrow an expression from Anne Buddle, “Tipu Mania,” with a view to providing a balanced view of Tipu Sultan the man and the statesman. This study is premised on the verdict of Joseph François Michaud who not only admires the Sultan’s courage and noble intentions but also laments his superstition, lack of discretion and farsight, apathy to deliberations, and counterproductive stubbornness that inevitably led to his undoing. Tipu’s tenacious conviction in the rectitude of his policies and measures deprived him of the sagacity to mend and amend them as and when necessary. The American gymnast and three-time Olympian Dominique Dawes observed that people do not plan to fail but respond to failure when it occurs by bouncing back and responding to it. Tipu Sultan’s misfortune was that he failed to learn from his failures.